"Goodbye Minitel, welcome to the internet". The Hourtin speech as a turning-point for French internet policy. Issue 4 (1st October 2020) - Bellon, Anne
Abstract: In 1997, the recently appointed French Prime Minister Lionel Jospin took a firm stance in favor of the Internet and announced an ambitious program to develop information technology and networks. In a country characterized by the lingering presence of the Minitel and bureaucratic reluctance to Internet solutions, this allocution, referred as the Hourtin speech, has been acknowledged as a turning-point in French internet policies. However, little is known about the dynamics that made such a statement possible. Based on interviews and personal archive of key actors, this paper offers to investigate the administrative and political processes that enabled such a change of position at the highest level of the State. While the role played by civil servants or government officials in promoting the development of the Internet in France has often been overlooked in internet histories, we offer new insight on the political work and administrative mobilizations that contributed to the diffusion of internet solutions and more broadly, to the advent of a digital revolution.